Pengaruh Penggunaan Endorsement dan Social Media Marketing Terhadap Keputusan Tamu Menginap di Hotel Harris Vertu Harmoni Jakarta - Widodo, Bambang; Jessica Carmelita (TOBA: Journal of Tourism, Hospitality, and Destination, 2022)
Competition in the hospitality business is getting tougher, encouraging hotels to continue to promote. Currently, online promotions that are quite effective are endorsements and social media marketing via the Instagram platform. One of the hotels that utilizes endorsement and social media marketing services is the Harris Vertu Harmoni Hotel Jakarta. This study aims to determine how much influence endorsements and social media marketing have on guests' decisions to stay at Hotel Haris Vertu Harmoni Jakarta partially and simultaneously. The quantitative method is this type of research using multiple regression formulas processed with the help of SPSS software. Data was obtained through a questionnaire from followers / people who had visited the hotel's Instagram (@hvertuharmoni) with a minimum age range of 18 years as many as 100 people. The results of the F test analysis with a significance value of 0.000 <0.005 can be obtained as a whole the endorsement and social media marketing variables significantly influence the guest's decision of 55.890. Meanwhile, the coefficient of determination test obtained a value of 0.535. The conclusion obtained is that there is a significant influence between the two independent variables on the dependent variable of 53.5%, while the remaining 46.5% is influenced by other factors.